Coccidiosis in japanese quails (Coturnix japonica): characterization of a naturally occurring infection in a commercial rearing farm - Teixeira,M (2004)
A study about coccidiosis in Japanese quails was carried out in order to identify species of the genus Eimeria and characterize a naturally occurring infection in a commercial rearing farm. For this purpose, fecal exams, oocyst counting and morphological study were performed, besides necropsy and histopathology to confirm diagnosis. Three species of the genus Eimeria were found and identified as E. tsunodai, E. uzura and E. bateri. The natural infection was characterized as subclinical because of the mild and nonspecific clinical signs. Nevertheless, coccidiosis was considered an important disease because endogenous stages of the parasites and a high number of oocysts in feces were associated with intestinal lesions. The results suggest that such infection might represent a limiting factor to this branch of the modern poultry industry.